Catastrophizing and anxiety sensitivity mediate the relationship between persistent pain and emotional eating. (1st August 2016) - Janke, E. Amy; Jones, Elizabeth; Hopkins, Christina M.; Ruggieri, Madelyn; Hruska, Alesha
Abstract: Stress-induced or "emotional eating" contributes to increased caloric intake and weight gain, yet models examining psychosocial factors that promote and sustain this behavior are incomplete. There is a need to identify explicit, clinically-relevant mechanisms of emotional eating behavior. Pain is a common stressor associated with increased weight and, potentially, altered eating behaviors. The present study applies the Fear Avoidance Model (FAM) of pain to examine processes that may explain the relationship between pain and increased weight while also providing the opportunity to examine specific mechanisms that may encourage eating during a variety of stressors. Our aim is to better understand the impact of pain on eating behavior and the potential for the FAM to improve our understanding of the psychological mechanisms that promote eating during times of duress. A survey of 312 adults explored the link between pain experience and stress-induced eating, further examining the mediating effects of the psychological aspects of the FAM (e.g., anxiety sensitivity, catastrophizing, and pain-related fear). 24% of respondents reported persistent pain, and had significantly higher BMIs than their pain-free peers. All three FAM components were positively correlated with measures of emotional, external, and restrained eating. Anxiety sensitivity and catastrophizing significantly mediated the relationship between persistent pain and emotional eating behavior, while anxiety sensitivity alone mediated the relationship between persistent pain and external eating. Findings suggest pain may be associated with increased likelihood for emotional eating and that characteristics from FAM, in particular anxiety sensitivity and catastrophizing, may mediate the relationship between the presence of persistent pain and emotional eating behavior. Evidence-based treatments targeting anxiety sensitivity and catastrophizing could be useful to address emotional eating in individuals struggling with both weight and chronic pain.